Perhitungan Harga Pokok Penjualan Pada UMKM di Cikarang: Studi Kasus Mie Ayam Bakso Sragen Mas Pri - Muhamad Syahwildan; Tutiek Indriani; Abel Nabila; Wini Nur Optaviani (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study highlights the importance of accurately calculating the Cost of Goods Sold (COGS) as a foundation for strategic decision-making in the operations of Micro, Small, and Medium Enterprises (MSMEs), specifically focusing on the business "Mie Ayam Bakso Mas Pri" located in Cikarang. The issue addressed is the challenge faced by MSMEs in accurately calculating COGS, which stems from a lack of knowledge, hidden or overlooked costs, and limited access to appropriate calculation methods. The primary objective of this research is to identify the cost components that influence COGS and to explore the implementation of calculation methods in a meatball processing business. This study employs a qualitative approach with a descriptive method. Data was collected through direct observation, interviews with the business owner and other relevant informants, and document analysis. The sources of data include primary data obtained directly from the MSME "Mie Ayam Bakso Mas Pri" and secondary data from various relevant literature. The research was conducted in the South Cikarang area, Bekasi Regency. The results from the methods used are expected to provide deeper insights into COGS management strategies in culinary sector MSMEs and their impact on operational efficiency and pricing decisions.